Pentingnya Menjalankan Etika Dalam Bisnis - Melia Br Ginting; Nuri Aslami (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
Summary of business Ethics is outside the provisions of the laws undanganStandar which is higher than the minimum standard according to the law.We often find that our business activities is the gray area that is not arranged.The rule of law.Ethical behavior in business activity is very important for the Business itself.Unethical business especially detrimental to the business itself From the perspective of the long-term.Good business is not just business baikMenguntungkan, but good business is different with a profitable business is Also a good business morally.The application of business ethics is taught in Islam, the Example of the Prophet offers many clues to the ethics of the store.As a branch of applied philosophy, business ethics focuses on the moral aspects of behavior.The person and the regulation of the profession in industripengelolaan.Therefore, business ethics can be considered as upayaMenerapkan ethical principles in the field of economic relations between people.